Dampak Inflasi dan Dana Pihak Ketiga terhadap Pembiayaan dengan Moderasi Pertumbuhan Ekonomi - Arifa Pratami (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2020)
Abstract - The study aims to analyze the impact of inflation and third-party funds on financing by making economic growth a moderating variable. The course uses secondary monthly-form data from January 2010 to December 2017 with Sharia banking objects. The data analysis technique used is the Error Correction Model (ECM) analysis. The study results found that first, inflation does not have a significant effect on financing in Islamic banking either directly or with the moderating variable of economic growth. Second, Third Party Funds (TPF) does not have a significant direct effect on financing. In contrast, with the moderating variable of economic growth, it is found that economic growth can moderate the influence of Third Party Funds (TPF) on financing in a negative direction. This study provides a recommendation that Islamic banking continues to increase the distribution of Third Party Funds (TPF) in the real sector while still utilizing short-term investment financing instruments in the form of Bank Indonesia Syariah Certificates (SBIS) to increase the level of bank profitability. Keywords: Sharia Banking, Inflation, Third-Party Funding, Economic Growth